PENGARUH CITRA MEREK, KESADARAN MEREK, DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA MR. SUPREK SURABAYA - Rantau, Aga Shanada; Andayani, Sri; Tjahjono, Endro (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACT In this globalization era, there are many chicken-based restaurants that have sprung up in all countries, such as in Indonesia, especially in Surabaya, we have found many chicken restaurants, one of the culinary processions of chicken that many people enjoy doing is chicken geprek. With a price that is quite affordable by all people processed by many geprek chickens bought by the public. This causes many to open businesses by selling geprek chickens of the same type with different appearance to give the characteristics of the products they sell to attract consumers. Mr. Suprek Surabaya is the place of this research. The purpose of this study is to determine how much influence the brand image, brand awareness, and product innovation on purchasing decisions. This type of research is quantitative research. The study population is consumers Mr. Suprek Surabaya. While the sample of 100 respondents used a non-probability method (non-random sampling) and data collection using a questionnaire. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that brand image, brand awareness, and product innovation have a strong influence on purchasing decisions at Mr. Suprek Surabaya. Based on these conclusions, it is hoped that Mr. Suprek Surabaya can further enhance the Brand Image, Brand Awareness, and Product Innovation variables on Purchasing Decisions to retain consumers and customers. Keywords: brand image, brand awareness, product innovation, and purchasing decisions